Thermodynamic Studies of the Molecular Interactions of p-Halophenols with Free Bases meso-Tetraarylporphyrins - Zabardasti, Abedien; Asadi, Mozaffar; Allah Karimivand, Vali; Ghasemi, Jahanbakhsh (Asian Journal of Chemistry, 2016)
The interactions of p-halophenols p-BrC6H4OH and p-ClC6H4OH with free base meso-tetraphenylporphyrins (H2T(4-X)PP; X= OCH3, CH3 H, Cl and H2T(3-X)PP; X = CH3, Cl) have been studied. The overall formation constants K (M–2) and the thermodynamic parameters were calculated by using UV-Vis spectrohptometry titration. The overall formation constants show the following trend with X substituent of porphyrins: H2T(4-CH3O)PP > H2T(3-Cl)PP > H2T(3-CH3)PP > H2T(4-CH3)P > H2TPP > H2T(4-Cl)PP On the other hand, p-BrC6H4OH forms more stable adducts with free base porphyrins than p-ClC6H4OH.